Pemetaan Skripsi Mahasiswa Pariwisata Universitas Pendidikan Indonesia Berdasarkan Kajian Bibliometrika - Eri, Resti Julvia (Tourism and Hospitality Essentials Journal, 2021)
The study aims to map out research for research-based on tourism at the Indonesian university of education. The bibliometric and co-word analysis is used to reveal characteristics and status on the research for tourism in UPI. Script data uploaded on repository.upi. edu during period 2012-2019. The title descriptor, year, study programs, writers, and key words from the authors are collected and analyzed and thus indicate that the most widely worded key words of MRL is ‘touris satisfaction’, at MPP is ‘visiting decisions’ and at MIK is ‘product innovation’. For the most concepts and theories of tourism used in MRL are the theories of 4 A (attraction, accesable, amenities, ancillary) and tourism psychology, at MPP are marketing theories promotion of tourism with characteristic tourist interest, while at MIK are the business economy and tourism accounting practice. In general the focus and inclination of research in the three major has been consistently fluid over the past eight years following Indonesia's actual tourism conditions and the concept of tourism theory used is relatively widespread, showing development efforts from each study program so that some of the hot theories are properly developed and tend to mature, some of the theories have great potential for further development, And many other theories are marginal and immature